Modelling Investment Decisions of an Industrial Organisation (on the example of “Zangezur Copper Molybdenum Combine” CJSC). - Nanyan, Ashot (Bulletin of Yerevan University G: Economics, 2018)
The present paper substantiates the necessity of promoting internal investments in the current stage of economic development of RA. We document that due to limitations in statistical data and the lack of diversification opportunities, commonly accepted scientific systems that support investment decisions, generally, do not apply to Armenian reality. For this reason, the paper aims to offer economic models that circumvent the foregoing deficiencies. The models are applied to two investment projects of “Zangezur Copper Molybdenum Combine” CJSC giving rise to plausible results.
Keywords: internal investments, diversification, net present value, payback period, optimization